Anchored in 'average thinking' in studies of arid rangeland dynamics – The need for a step forward from traditional measures of variability. (May 2015) - Easdale, M.H.; Bruzzone, O.
Abstract: There is a wide consensus that arid and semi-arid environments are highly variable in space and time. The most frequent approaches to describe and analyze arid and semi-arid rangelands are based on the usage of averages and Normal distributions as main references to describe spatial and temporal differences. We argue that rangeland ecology science should move forward in methods to better capture the patterns of rangeland dynamics, rather than just focusing on simple measures of variability. We provide different simulated time series data in order to illustrate the limitations of some currently used methodologies. We call for the application of time series methods in order to better understand complex dynamics in arid and semi-arid rangelands. Highlights: Arid and semi-arid rangelands are highly variable in space and time. Most frequent approaches to study temporal variability are based on averages and Normal distributions. Research should study patterns of rangeland dynamics, rather than simple measures of variability. We call for the application of time series methods to tackle ecosystem dynamics.